Albert Camus - Olivier Todd (Európa Könyvkiadó, 1996)
On September 22, 1913, on the Saint-Paul Farm outside the town of Mondovi in Algeria, Lucien Auguste Camus wrote to his employer, "The grape harvest at Saint-Paul ended this morning at 10 a.m."
Metadonnees Open Library
Keywords: mythe sisyphe; cuisine francaise; sisyphe; francaise; absurde